2005
DOI: 10.1002/psc.692
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of pentacyclo‐undecane cage peptides of the type [Ac‐X‐Y‐NHMe]

Abstract: The conformational preferences of peptides of the type, Ac-X-Y-NHMe, where X and Y = Ala, cage and Pro, were studied by means of computational techniques within the framework of a molecular mechanics approach. For each of the eight peptide analogues, extensive conformational searches were carried out using molecular dynamics (MD) and simulated annealing (SA) protocols in an iterative fashion. Both results are in good agreement and complement each other. The conformational search indicates that the cage residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Statistical methods are required to ensure that the chances of finding new unique conformations are rather small (see Figure 6). 171 Electronic structure or quantum mechanical (QM) methods based on quantum chemical theory are the most accurate but most expensive calculations in terms of computational resources and time. Such methods include ab initio 176,177 including density functional theory (DFT) 90 Semiempirical methods use QM calculations only for the valence electrons in the system and make drastic approximations for the other electrons as well as the behavior of the atom nuclei.…”
Section: Enzyme−inhibitor Interactions: Amentioning
confidence: 99%
“…Statistical methods are required to ensure that the chances of finding new unique conformations are rather small (see Figure 6). 171 Electronic structure or quantum mechanical (QM) methods based on quantum chemical theory are the most accurate but most expensive calculations in terms of computational resources and time. Such methods include ab initio 176,177 including density functional theory (DFT) 90 Semiempirical methods use QM calculations only for the valence electrons in the system and make drastic approximations for the other electrons as well as the behavior of the atom nuclei.…”
Section: Enzyme−inhibitor Interactions: Amentioning
confidence: 99%
“…The structural tendencies of other cyclopropane derivatives such as c 3 Val51,52 or other 2-phenyl-1-aminocycloalkanecarboxylic acids such as c 5 Phe53 and c 6 Phe5456 have also been reported. Additionally, the theoretical study of 8-aminopentacycloundecane-8-carboxylic acid has been reported 57. Very recently, the helical screw sense exclusively governed by chiral centres in the side chain of some cyclic amino acids has been reported 5860…”
Section: Introductionmentioning
confidence: 99%
“…By performing annealing (i.e., slow cooling) from a high temperature, the peptide is able to surmount energetic barriers towards lower energy conformations. This method has been used in a number of gas phase peptide studies 4447. Ten copies of each of these peptides were annealed from a starting temperature of 1000 K and slowly cooled towards 0 K. The temperature was maintained by using the stochastic thermostat developed by Bussi et al 48.…”
Section: Methodsmentioning
confidence: 99%